The Conceptual Model Of Crisis Management In Facing The Covid-19 Pandemic For Tourism Destinations - Tri Wahyuningsih; Antin Okfitasari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The study aims to find a crisis management model in the tourism system affected by COVID-19. This study uses a thematic analysis approach to systematically examine the literature. The results of the literature review show that the COVID-19 system and impacts include psychological, health, social, economic, cultural, technological, environmental, and political perspectives. A large amount of literature has described the phases of crisis management in tourism. Management must address disruptive events at three stages before, during, and before. In this way, in the case of industry, stakeholders can react, design, and reorganize new approaches to deal with impending crises. The results of the study also show that measures to deal with the crisis in the tourism sector, in particular, can be carried out through four stages of the resilience cycle, namely system collapse, reorganization, growth, and consolidation.